Penguatan Ekonomi Rumah Tangga Petani Kopi Perempuan Nagari Lubuk Malako Berbasis CBR - Sri Ramadhan; Wushi Adilla Arsyi; Rama Wahyudin; Randi Isdendi (STMIK Royal, 2026)
Abstract: This study employs the Community-Based Research (CBR) model to empower female coffee farmers in Nagari Lubuk Malako, South Solok, addressing low economic literacy and limited market access. By engaging the community as active partners, the research implemented post-harvest training, entrepreneurship literacy, and digital marketing strategies. Results indicate a significant capacity increase, evidenced by the formation of a women's business group, the launch of the local brand “Kopi Lubuk Malako,” and improved skills for 80% of participants. Key outcomes include enhanced household income, strengthened local economic institutions, and increased female independence in decision-making. Supported by local government and leaders, this program also facilitated business legality and halal certification. This study concludes that the CBR model is an effective and sustainable strategy for strengthening the household economy and fostering the empowerment of women in the agricultural sector. Keywords: the role of women; coffee farmers and CBR Abstrak: Studi ini menggunakan model Penelitian Berbasis Komunitas (Community-Based Research/CBR) untuk memberdayakan petani kopi perempuan di Nagari Lubuk Malako, Solok Selatan, dengan mengatasi rendahnya literasi ekonomi dan terbatasnya akses pasar. Dengan melibatkan masyarakat sebagai mitra aktif, penelitian ini menerapkan pelatihan pasca panen, literasi kewirausahaan, dan strategi pemasaran digital. Hasil menunjukkan peningkatan kapasitas yang signifikan, dibuktikan dengan pembentukan kelompok usaha perempuan, peluncuran merek lokal “Kopi Lubuk Malako,” dan peningkatan keterampilan bagi 80% peserta. Hasil utama meliputi peningkatan pendapatan rumah tangga, penguatan lembaga ekonomi lokal, dan peningkatan kemandirian perempuan dalam pengambilan keputusan. Didukung oleh pemerintah dan pemimpin lokal, program ini juga memfasilitasi legalitas usaha dan sertifikasi halal. Studi ini menyimpulkan bahwa model CBR merupakan strategi yang efektif dan berkelanjutan untuk memperkuat ekonomi rumah tangga dan mendorong pemberdayaan perempuan di sektor pertanian. Kata Kunci : peran perempuan; petani kopi dan CBR